Pencalonan Anggota Legislatif Perempuan pada Pemilu Tahun 2024 (Perspektif Undang-Undang Partai Politik) (Studi di Kab. Lombok Timur) - Lusiana Damayanti; Rr. Cahyowati; M. Saleh (Bagian Hukum Tata Negara Fakultas Hukum, Ilmu Sosial, dan Ilmu Politik Universitas Mataram, 2024)
This research aims to determine the candidacy of female legislative members in the 2024 General Election in East Lombok Regency (Political Party Law Perspective and find out the obstacles and solutions to nominating female legislative members in the 2024 General Election in East Lombok Regency (Political Party Law Perspective). The type of research used is empirical legal research. The research results show that in the nomination of female legislative members in the 2024 elections in East Lombok Regency17, political parties have fulfilled the 30% requirement mandated by Law Number 12 of 2011. There is one political party that has fulfilled its requirements. Where there are no legislative candidates, whether male or female legislative candidates. The nomination of female legislative members has been running well and under the law’s mandate. However, one party has not fulfilled these provisions because they do not have legislative candidates. Keywords: Woman, General Election, Political Parties